Software defined data center network with hybrid routing - Yue-ping CAI; Chang-ping WANG (Tongxin xuebao, 2016)
In the current data center networks, the flow size distribution is not uniform and the transmission performance requirements of elephant flows and mice flows are different. To address this issue, a software-defined hybrid routing (SHR) scheme was proposed. SHR differentiate data flows by statistical calculat nt flows utilize the adap-tive routing algorithm while the mice flows use the oblivious routing algorithm. SHR extends the OpenFlow scheme by offloading some basic functions such as flow statistical detection and mice flow forwarding to switches to reduce the switch-controller interaction overhead. Performance evaluations of SHR were carried out using the fat-tree network to-pology. Results show that SHR can effectively increase network throughput and reduce the flow dropping rate as well as packet delay compared with the traditional ECMP algorithm.